Experimental investigation and demonstration of pilot-scale combustion of oil-water emulsions and coal-water slurry with pronounced water contents at elevated temperatures with the use of pure oxygen. (15th December 2020) - Gaber, Christian; Wachter, Philipp; Demuth, Martin; Hochenauer, Christoph
Graphical abstract: Highlights: Oxy-fuel combustion of oil–water emulsions with water contents of up to 75 wt%. Oxygen enriched combustion of coal-water slurry from pyrolytic carbon black. Thermal efficiencies of 45% and higher at an exhaust gas temperature of 1100 °C. Successful combustion with oxygen enrichments between 50 and 100 vol.%. A pronounced water content resulted in a flameless oxy-fuel combustion. Abstract: In this study, a high-temperature combustion chamber was fueled with oil-water-emulsions (OWE) and coal-water-slurry (CWS) from pyrolytic carbon black in order to experimentally examine the feasibility of co-processing low-calorific value fuels in industrial high-temperature applications by using pure oxygen as oxidizer. The present paper is the first report on the oxy-fuel combustion characteristics of liquid fuels with a pronounced water content including flame characteristics, temperature distribution, thermal output and emission measurements in a semi-industrial combustion chamber at a thermal input of 300 kW and ambient pressure. The obtained results demonstrated the beneficial character of oxy-fuel combustion and showed that co-processing of OWE and CWS from pCB with pronounced water contents is technically feasible. A stable oxy-fuel combustion of OWE was achieved with water contents of up to 75 wt%. In addition, a successful combustion of CWS with a water content of 65 wt% and oxygen concentrations above 50 vol.% was observed. The obtained results further demonstrated the beneficial character of oxy-fuel combustion of OWE and CWS especially with regard to reduced NOx emissions. The combustion of OWE with a water content of 75 wt% resulted in a significant reduction of the NOx concentration compared to pure heating oil, namely from 760 to 110 ppm, whereas the maximum temperature of the combustion chamber decreased only slightly, while in the case of CWS combustion, the concentration of CO emitted decreased significantly from 34 to 9 ppm by increasing the oxygen concentration in the oxidizer from 50 to 100 vol.%.